Knights and castles : a nonfiction companion to The knight at dawn - Osborne, Will.; Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Jack and Annie look at knights, armor, and life in a castle.
"A Stepping Stone book."
Includes bibliographical references (p. 110) and index.
4.3
3-6
3-6.
690
Keywords: Knights and knighthood -- Europe -- Juvenile literature; Castles -- Europe -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Knights and knighthood; Castles; Civilization, Medieval; Knights and knighthood; Castles; Medieval civilization